2021
DOI: 10.1186/s12960-021-00667-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the rural and remote practice of medical workforce in Maluku Islands of Indonesia: a cross-sectional study

Abstract: Background Many factors contribute to engagement in rural and remote (RR) medical practice, but little is known about the factors associated with rural and remote medical practice in such remote locations as the Maluku Province of Indonesia. This study describes factors associated with actual RR practice, preferred RR practice, and intention to remain practice in Maluku Province. Methods An online survey of work-related experience and intentions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…[17,18] Although PUFM has no stated policy/quota for rural background students, each year it admitted 20-25% of students from rural and remote districts, both districts without or with the memorandum of understanding (MoU) with the faculty. [3,19] The selection was done on two levels, by the district's officers for screening purposes and later by the university. However, the selection procedure was not documented in detail.…”
Section: A1 Get the "Right Student"mentioning
confidence: 99%
See 3 more Smart Citations
“…[17,18] Although PUFM has no stated policy/quota for rural background students, each year it admitted 20-25% of students from rural and remote districts, both districts without or with the memorandum of understanding (MoU) with the faculty. [3,19] The selection was done on two levels, by the district's officers for screening purposes and later by the university. However, the selection procedure was not documented in detail.…”
Section: A1 Get the "Right Student"mentioning
confidence: 99%
“…[24,33] However, for the medical internship, the salary and incentives known as Basic Living Expenses (BLE) are smaller and deemed to have not met the necessities of life compared to the volume of work assigned to the interns. [33,34] Besides the support given to their physicians with bonded placements, most districts also provide incentives for physicians from national employment schemes such as Nusantara Sehat and PGDS. Hence, these physicians with national appointments receive extra incentives.…”
Section: B4 Tie Education Subsidies To Mandatory Placementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the decisions of health workers to practice rurally are informed by non-financial incentives, including job satisfaction, career advancement opportunities, and professional development [ 12 ]. Other studies have identified strategies to sustain rural health workforce, including recruiting more doctors with rural background [ 13 , 14 , 15 ], longer rural immersions and regional training [ 14 , 15 , 16 ], and enhancing rural training opportunities and sustainable rural working condition for overseas trained doctors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%